Influencia del autoestima en el aprendizaje significativo en lo estudiantes de 4to. año de la Escuela de Educación Básica “5 de Junio” - Moran Diaz, Hilda Gabriela (2019)
The case study work entitled: INFLUENCE OF SELF-ESTIMATE IN THE SIGNIFICANT LEARNING OF 4th. YEAR OF THE SCHOOL OF BASIC EDUCATION "JUNE 5", which was based on observing the factors that affect or generate low self-esteem in students and how this influences significant learning in the group of students chosen for this case. Especially in monitoring the levels of self-esteem in the students of the school in question, in order to identify the factors that are presented in a group of students, and to be able to make a contribution with data that can be used by teachers, to achieve the best level of self-esteem in their students and that they use an adequate methodological with new procedures to guarantee a better meaningful learning in them. In this study, a series of techniques and instruments for data collection, direct observation, and a basic follow-up were used to obtain data on the level of performance in various partials of the students under study. For the preparation of the report, he made the objective statement, proceeding to statistically analyze the data obtained, thus being able to establish the corresponding conclusions